Cathepsin-K Targeted by Sanggenol L Induces Lethal Autophagy through ROS-Dependent AMPK/mTOR Signaling in Gastric Cancer - Kui Zhang; Xin Hu; Jingjing Su; Guangzhao Pan; Abhimanyu Thakur; Natalia Baran; Anne Dijkstra; Isha Gaurav; Zhijun Yang; Hongjuan Cui (Pharmacological Research - Modern Chinese Medicine)
Introduction: Sanggenol L (Sang gen chun L) is a bioactive flavonoid derived from Morus alba (Sang bai pi), a traditional Chinese medicine widely used for clearing lung heat, promoting blood circulation, and reducing inflammation. Gastric cancer (GC) remains one of the most lethal malignancies worldwide, with limited effective treatments for advanced or metastatic stages. Natural products, including those from traditional Chinese medicine (TCM), are promising sources for new anticancer compounds, warranting further investigation. Methods: The study delved into the antitumor characteristics of Sanggenol L, a natural derivative extracted from the root bark of mulberry (Morus alba L.) trees. Both in vitro and in vivo investigations conducted to elucidate its mechanisms of action against GC cells. Results: Sanggenol L demonstrated effective inhibition of GC cell growth and proliferation in a dose-dependent manner, along with induction of cell cycle arrest, autophagy and apoptosis. Notably, Sanggenol L activated lethal autophagic flux and induced GC cell apoptosis by triggering the AMPK/mTOR signaling pathway via reactive oxygen species (ROS). Importantly, Sanggenol L targeted cathepsin K, leading to a significant reduction in its proteolytic activity in both in vitro and in vivo. Furthermore, overexpression of CTSK partially counteracted the growth-inhibitory and pro-apoptotic effects of Sanggenol L by reducing ROS levels induced by the compound. Noteworthy is the significant overexpression of CTSK in cancerous tissues, particularly in GC, compared to adjacent or normal tissues, with its upregulation correlating with poor prognosis, suggesting its potential as a therapeutic target in GC treatment. Conclusion: Sanggenol L exhibits potential therapeutic efficacy against GC, primarily through its ability to modulate the ROS/AMPK/mTOR pathway and by targeting cathepsin K, which has emerged as a promising anticancer target.